If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying b + (-6) = 6 b + -6 = 6 Reorder the terms: -6 + b = 6 Solving -6 + b = 6 Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + b = 6 + 6 Combine like terms: -6 + 6 = 0 0 + b = 6 + 6 b = 6 + 6 Combine like terms: 6 + 6 = 12 b = 12 Simplifying b = 12
| 12-(2y-4)=8 | | 6(7-u)+u=36+4 | | Q+918=451 | | 2-(x+3)=4 | | y=1.3x-7.8 | | 20x=300 | | 2g+3g-6+10=14 | | 25x=40 | | 0.5+1.9=10.4 | | 3ab(a^2)= | | 5p-14=8p+1 | | 24(15a)=123 | | 3ab+5b= | | 9d-7+4d=3d-17 | | 750-50h=0 | | 6x-y=-15 | | 5b^2(2b^5)= | | 2x^2-2x+3=y | | (s-2)(s-2)-s^2=20 | | -185+35h=0 | | -3+x-5=25 | | 6h-12=-4h-18 | | 3(4-5x-6x)+8(3x+8)=4 | | x+1/5=4 | | m^3+6m^2-16m=0 | | 50=15-6(2s-5) | | 5-6p=5-9p | | 250/20= | | 0.4(2x+4)=4.8 | | -5(-10-a)=60 | | 8x+9y=18 | | 44=4x-12 |